634. Chlorhexidine Oral Rinses to Alter the Oral and Sputum Microbiota in COPD (CLIMB): a Randomized, Double-blinded, Placebo-controlled, Parallel-group Pilot Study. (31st December 2020) - Pragman, Alexa; Fieberg, Ann; Reilly, Cavan; Wendt, Chris
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a progressive, inflammatory lung disease with few available disease-modifying therapies. Acute exacerbations of COPD (AECOPD) increase morbidity and mortality, and their occurrence coincides with sputum and oral microbiota dysbiosis. The oral microbiota also serves as the source of the lower airway microbiota. Chlorhexidine oral rinses are known to alter the oral microbiota. We hypothesized that subjects randomized to 8 weeks of chlorhexidine oral rinses (vs. placebo) will demonstrate decreased microbiota biomass compared to baseline and those on placebo. Methods: We performed a randomized, double-blind, placebo-controlled, 8-week study of the effects of twice-daily chlorhexidine oral rinses on 44 subjects with COPD. Baseline and post-treatment data were obtained evaluating oral and sputum microbiota biomass and composition, systemic inflammation (CRP, fibrinogen, and WBC count), and respiratory symptoms (Breathlessness, Cough, and Sputum Scale [BCSS], St. George's Respiratory Questionnaire [SGRQ], and AECOPD assessment). All analyses were prespecified. Results: Forty of 44 participants completed the study. The primary analysis of the mean differences in oral and sputum microbiota biomass between treatment groups was not significant. Chlorhexidine use was associated with a decrease in oral and sputum microbiota alpha diversity compared with placebo (Shannon diversity index change [standard error]: -0.349 [0.091] and -0.622 [0.169] respectively; padj =0.001 for both). There was no significant change in CRP, fibrinogen, WBC count, or BCSS score between treatment groups over the study period. Chlorhexidine use was associated with a significant improvement in SGRQ score when compared to the placebo (mean change ± standard deviation: chlorhexidine -4.7 ± 8.0 vs. placebo 1.7 ± 8.9, p=0.011; minimal clinically important difference in SGRQ score -4). Few adverse events were reported. Conclusion: Among those with COPD, use of twice-daily chlorhexidine oral rinses resulted in decreased oral and sputum microbiota alpha diversity and clinically significant improvement in COPD symptoms. Chlorhexidine use did not result in decreased oral or sputum microbiota biomass or decreased systemic inflammation. Disclosures: All Authors : No reported disclosures